Communication from the Commission to the European Parliament and the Council - European Commission, -
The European´s Union Communication highlights the valuable linkages between European Union and the Arctic Region. It explains the Europe´s interest in the Arctic as the valuable source of natural living and non - living resources. It contains highlights on European Union´s strategy towards the Arctic.